Enhancement of CD8+T cell cytotoxicity activity by IFN-α implies alternative pathologic role in systemic lupus erythematosus - Chen-xing Zhang; You-ying Mao; Yu-pin Tan; Mei-yu Zhang; Kang Shao; Shu-jun Wang; Ping Ji; Jia-yuan Wang; Lei Yin; Ying Wang (Journal of Translational Autoimmunity)
Objective: Systemic lupus erythematosus (SLE) is a heterogeneous autoimmune disease which is affected by the environmental, genetic factors as well as the immune system. Previous reports have implicated IFN-α in the pathogenesis of SLE. Up to date, however, no research has ever investigated the effect of IFN-α on CD8+T cells, which might be implicated in the pathogenesis of SLE. In the present study, we aimed to explore the pathologic role of IFN-α in regard to dysfunction of CD8+T cells in SLE. Methods: Serum level of IFN-α was detected in SLE and healthy controls (HC). Surface expression of lysosome-associated membrane protein 1 (LAMP-1; CD107a) and secretion of granzyme B of CD8+T cells was measured in SLE and HC with or without IFN-α co-stimulation/PI3K inhibitor. Results: Our results demonstrated that there was increased surface expression of CD107a of CD8+T cells in SLE patients compared with healthy controls (HC), indicating enhanced cytotoxicity of CD8+T cells in SLE patients. Meanwhile, increased secretion of granzyme B was also detected in CD8+T cells of SLE compared with HC, which correlated with the disease activity (SLEDAI). Furthermore, elevated serum level of IFN-α in SLE was confirmed in our study. In vitro study, granzyme B secretion by CD8+T cells was upregulated upon IFN-α costimulation, which was consistent with enhanced cytotoxicity of CD8+T cells upon IFN-α costimulation, as reflected by elevated surface expression of CD107a. PI3K inhibitor reversed increased granzyme B synthesis upon IFN-α costimulation in a dose-dependent manner. Conclusion: In summary, elevated serum level of IFN-α was responsible for increased secretion of granzyme B and enhanced cytotoxicity of CD8+T cells in SLE and this process may be related to PI3K pathway. Relevant molecules and mechanism remains to be explored in the future.